The MPI-SOUSY-VHF Radar at Jicamarca: high altitude-resolution capabilities - Woodman Pollitt, Ronald Francisco (2007)
The MPI-SOUSY radar has been moved from its original location at the Harz Mountains, Germany, to the Jicamarca Observatory. Two main modifications have been made to the system: 1) The antenna array now consist of 126 Yagis deployed in an square array of 16x16, 4 element Yagis, similar to the original ones, and 2) the control and data acquisition system has been modernized as described later on. The phase steering system has not been implemented yet, but is planned for the future.